(untitled) (American Journal of Islam and Society, 2001)
Writing is certainly one of man’s greatest inventions, and good writing is a skill which elevates one’s position in the society of the learned. The other side of the coin is poor writing that leads to poor communication and often miscommunication between the writer and the reader(s). Writing in the academic world is all the more important, as it is the only means of scholarly expression. The quality of good writing skills is a cause of concern for many teachers at various stages of education, especially at the tertiary level. This is perhaps more true of students whose native language is not English, and for lecturers who have to teach such students. The book under review is a collection of essays written by lecturers and writing specialists primarily at the University of Western Cape (UWC). It is divided into six major parts and fourteen chapters. The essays are written on various themes that provide guidelines for developing writing skiUs in the academic setting. The book is edited by Brenda Leibowitz, Director of the National Center for Curriculum Research and Development at the Department of Education, and Yasien Mohamed, a senior lecturer in the Department of Foreign Languages at UWC. The editors have compiled this book with the aim of providing insight, reflection, and guidelines that would empower lecturers to teach their subject more effectively and especially to help students with the writing aspect of their university study. Mohamed, who wrote the introduction to the book, comments that writing and its development should be viewed as a "humanistic" activity, which recognizes the natural and creative forms of personal narrative writing, as opposed to a scientific approach, where writing is viewed as a product rather than a process. Actually, this empathetic approach to writing development is evident lhroughout the book. Part I of the book consists of one chapter only and deals with the importance of writing and teaching in the academia, emphasizing the need for lecturers to be evaluative of their own writing practices. Basing the advice on many years of experience as a trainer of writing, the author suggests many useful writing strategies including the use of dialogic materials, mind mapping, free writing, and writer’s support groups. Part II deals with diversity, culture, and writing, and consists of chapters ...